Analysis of Taboo Words with Racist Language in USA Today YouTube Account by Photographer to Stray Kids at 2024 Met Gala - Diva Ega Pramasa Ristian; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2024)
This study focused on a viral phenomenon that became a public conversation on social media and analyzed the Taboo word with the racist language spoken by a Photographer at the Met Gala 2024 who disrespected the boy group Stray Kids. This research uses qualitative methods and sociolinguistic approaches. This analysis follows Creswell's (2009) theory for data analysis techniques. Data analysis using Battistella's theory (2005) to discover the types of taboo words and Carmichael and Hamilton's theory (Liliweri 2018) regarding racist language in the USA Today YouTube account about photographers at the 2024 Met Gala event. Based on the analysis, taboo words were found according to the categories of Epithets, Profanity, and Obscenity. In addition, racist language is also found, namely one type of racist language which is included in two categories, namely stereotypes based on Race and race discrimination. The use of taboo words with racist language is considered commonplace by people from different countries, such as in this study a photographer who is of American descent and the boy group Stray Kids from South Korea. It can be concluded that the photographers who have committed these racist acts are because of their appearance during the photo session on the red carpet and also the different national origins of all Stray Kids members.